2019
DOI: 10.1016/j.matt.2019.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Printable Smart Pattern for Multifunctional Energy-Management E-Textile

Abstract: A facile one-step fabrication of coaxial fiber-based smart patterns for E-textile through 3D printing equipped with a coaxial spinneret is reported. Versatile smart textiles for different purposes can be fabricated by selecting different materials in construction of the coaxial layers. Examples such as silk energy-harvesting textile and energy-storage textile with superior performance are demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
175
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 196 publications
(175 citation statements)
references
References 24 publications
0
175
0
Order By: Relevance
“…Due to low cost, high efficiency, and mature technology, it is very possible to realize the large‐scale production of this energy harvesting fiber. Printing as one of effective methods for mass production has also been adopted to prepare a SE‐mode single fiber‐based TENG by using CNTs as a conductive core and silk fibroin as a dielectric sheath . Unfortunately, stretchability is absent in the above SE mode single fiber‐based TENGs due to the existence of straight core fiber.…”
Section: Triboelectric Nanogeneratorsmentioning
confidence: 99%
“…Due to low cost, high efficiency, and mature technology, it is very possible to realize the large‐scale production of this energy harvesting fiber. Printing as one of effective methods for mass production has also been adopted to prepare a SE‐mode single fiber‐based TENG by using CNTs as a conductive core and silk fibroin as a dielectric sheath . Unfortunately, stretchability is absent in the above SE mode single fiber‐based TENGs due to the existence of straight core fiber.…”
Section: Triboelectric Nanogeneratorsmentioning
confidence: 99%
“…Recently Zhang and co‐workers reported direct printing of core‐sheath fiber‐based smart patterns for energy/management E‐textile, using CNTs as a conductive core and silk fibroin as a dielectric sheath. [ 175 ] Chen and co‐workers demonstrated that it was possible to fabricate the asymmetric GO/polyaniline (PANi) microsupercapacitors using 3D extrusion printing which exhibits improvement in the voltage window, energy density, power density, and cycling stability compared with the symmetric microsupercapacitors. [ 176 ] Photodetectors consisting of semiconducting polymer poly(3‐hexylthiophene) (P3HT):[6,6]‐phenyl C61‐butyric acid methyl ester (PCBM) blend were printed via a layer‐by‐layer deposition process.…”
Section: Retaining Materials Properties Of Printed Polymersmentioning
confidence: 99%
“…Alternative techniques have been developed to fabricate conductive textiles, such as integrating metal filaments with yarns, coating fibers with a thin layer of conductive materials (metal nanoparticles/nanowires, carbon nanotubes, graphene, etc. ), or direct patterning of conducting polymers, and inkjet/stencil/screen/nozzle printing of conductive materials onto textiles ( Figure ) . The inclusion of metal wires in the yarns would increase the stiffness of the textiles and thereby decrease the wear comfort.…”
Section: Materials Designsmentioning
confidence: 99%
“…d) Photos showing the textiles are flexible and can be twisted and folded. Reproduced with permission . Copyright 2019, Elsevier.…”
Section: Materials Designsmentioning
confidence: 99%